New islamic movements in contemporray world: ideological projects and political activity (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the ideology of new Islamist movements in the modern world. Religious worldview as a form of social consciousness has the most significant impact on the formation of socio-political attitudes of believers that prove the legality of the use of violence in religious relations, or can contribute to the formation of such attitudes. Religious literacy is not limited to the narrow framework of obtaining religious and religious knowledge, it also involves a certain level of knowledge in general, the formation of political consciousness and political culture, legal consciousness and legal culture, knowledge of the history of their own people and world culture, knowledge of global trends, the basics of modern geopolitics, because today often religious ideas are exploited for the sake of certain geopolitical interests. The logical result of the negative development of Islamic radicalism and fundamentalism is extremism, which is turning into its extreme form of terrorism. In order to prevent these dangerous phenomena, it is necessary to deeply understand the causes and factors that give rise to Islamic radicalism and, on this basis, to take effective preventive measures. The solution to the problem of radicalization and extremism is inextricably linked to personnel who, in addition to philosophical and analytical knowledge, must possess deep theological knowledge.Key words: Islamist radicalism, traditionalism, fundamentalism, destabilization.